Associação dos polimorfismos de DNA dos genes dos colágenos 1 e 3 e o prolapso de órgãos pélvicos em mulheres brasileiras - Batista, Nilce Coimbra [UNIFESP] (2019)
Introduction: Pelvic organ prolapse (POP) has a multifactorial etiology that includes environmental and genetic factors. Several studies have investigated the association between COL1A1 and COL3A1 and POP polymorphisms. However, the results presented show differences between the populations analyzed. Objective: To compare the presence and frequency of COL1A1 and COL3A1 polymorphisms in patients with advanced POP (stages III and IV) and in women without POP in the Brazilian population. Methods: A case-control study that included 826 patients was divided into case (n = 348) and control (n = 286) groups. Peripheral blood DNA was extracted and the real-time polymerase chain reaction (RT-PCR) technique was used to determine genotyping of the samples. The programs SPSS (Chicago, USA) and GraphPad Prism 5.0 (California, USA) were used for statistical analysis, considering p <0.05 as statistically significant. Results: The case group had a mean age (68.03 years) higher than the control group (60.39 years) with p <0.0001. Regarding obstetric history, we observed a higher number of pregnancies, number of vaginal deliveries (normal and forceps) and higher newborn weight in women in the case group compared to the control group, p<0.05. On the other hand, women in the control group had a higher number of cesarean deliveries, p<0.0001. Regarding the COL1A1 and COL3A1 genotypes, no differences were observed in univariate and multivariate analyzes (p> 0.05). In the analysis of clinical factors, it was observed that women who had systemic arterial hypertension (SAH) [OR = 2.16; p=<0.0001], Diabetes Mellitus (DM) [OR = 2.48; p=<0.0001], varicose veins [OR = 1.60; p=0.016], heart disease [OR = 2.92; p=0.016] and family history (AFPOP) [OR = 1.82; p=0.010] had an increased risk for POP. Logistic regression model 1 reinforced vaginal delivery [OR = 10,582; p=0.000], the presence of heart disease [OR = 3.082; p=0.005), DM [OR = 2.509; p=0.016], AFPOP [OR = 2.493; p=0.007], HAS [OR = 2.118; p=0.013] and the number of pregnancies [OR = 1.225; p=0.001] as risk factors for POP. Regression model 2, on the other hand, showed that vaginal delivery [OR = 11,236; p=0.000], AFPOP [OR = 2.072; p=0.002], the number of pregnancies [OR = 1.283; p=0.000] and age [OR=1,096; p=0,000 as risk factors for POP. Meanwhile, Caesarean delivery was considered a protective factor for POP [OR = 0.431; p=0.000]. Conclusion: The distribution of COL1A1 polymorphism (rs1800012) and COL3A1 (rs1800255) wasn’t considered a risk factor for this disease. However, vaginal delivery, AFPOP, number of pregnancies, DM, and age were considered risk factors, and cesarean delivery was a protective factor for the development of POP.